Identifying critical success factors for successful BIM-FM implementation in construction projects - Özfurat, Bensu Namlı. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
The use of BIM (Building Information Modeling) in FM (Facility Management) is becoming increasingly common around the world, but despite a large number of studies focusing on BIM implementation success in design and construction, there is still no consensus on how to evaluate BIM-FM integration success. The primary goal of this research is to identify and prioritize BIM-FM related CSFs and offer an Analytic Network Process (ANP) model to evaluate factors in construction projects carried out by Turkish contractors. Its purpose is to provide some guidance on how to make BIM-FM deployment more efficient. It also intends to acquire insights on the state of BIM-FM integration in Turkey from professionals working in the Turkish construction sector who are specialists in BIM-FM processes, as well as interpret the CSFs listed. To achieve these objectives, identified CSFs are grouped into stakeholders-related, technology-related, design-related, and handover process related factors. The focus group sessions are used to collect data on interrelationships and relative importance ratings. ANP is then used to compute the priorities and importance weights. “BIM education and training for employees”, “Top leadership backing and motivation”, “Availability of capable/experienced personnel (both in FM and AEC)”, “Early involvement of Facility Managers in the BIM process”, “Using BIM to maximize potential cost savings (return on investment of built assets)” success factors and “stakeholders related factors and “design process-related factors” groups are among the essential findings of this study. Interviews are used to evaluate the final CSFs list and obtain input on the current status of BIM-FM integration in the Turkish construction sector and assess the advantages and barriers to BIM-FM integration indicated in the literature. This model gave industry representatives a way to analyze the effectiveness of their BIM-FM integration. The suggested model’s findings may help FM and AEC organizations review their projects and take the required steps to ensure project success.
Keywords: Building information modeling.; Facility management.